AB0321 A Totality-of-The-Evidence Approach To The Development of GP2015, A Proposed Etanercept Biosimilar. (15th July 2016) - McCamish, M.; DaSilva, A.; Ernst Mayer, R.; Fritsch, C.; Schiestl, M.
Abstract : Background: Assessment of biosimilarity uses the "totality-of-the-evidence" concept, whereby a complete data package, comprising physicochemical, biological, nonclinical and clinical data, is used to evaluate and confirm biosimilarity between a proposed biosimilar and an approved originator (reference) product. A stepwise approach, using comparative analytical characterisation to inform next steps, is recommended. The totality-of-evidence derived from these data should demonstrate that the active substance of a biosimilar and its originator are essentially the same. Objectives: To describe the development of a proposed etanercept biosimilar (GP2015). Methods: To define the development target, multiple batches of the originator were characterised over time to understand quality attributes relating to protein structure, function, and amino acid modifications. An iterative, target-directed development process was used to design and produce a potential biosimilar product (GP2015) that fell within the variability range of the originator. Biosimilarity between GP2015 and the originator was confirmed at analytical, functional, nonclinical, pharmacokinetic (PK) and clinical levels using a stepwise approach. Biochemical attributes and functional properties were assessed using a comprehensive and sensitive state-of-the-art panel of analytical tools. Bioequivalence between GP2015 and the originator was assessed in vivo and in four PK studies in healthy volunteers. To confirm there were no clinically meaningful differences between GP2015 and the originator, a study of efficacy, safety and immunogenicity was performed in patients with moderate-to-severe chronic plaque-type psoriasis. This confirmative study assessed the Psoriasis Area and Severity Index response rate at Week 12 and at long-term timepoints. Results: GP2015 was developed at the same dosage and strength as the originator. Multiple orthogonal analytical methods showed high similarity between GP2015 and the originator. The amino acid sequence was confirmed to be identical and protein folding was indistinguishable. Other attributes, such as glycosylation and product-related impurities, were highly-comparable with the originator. In vitro assays reflecting mechanisms of action and pharmacological properties showed GP2015 and the originator had similar bioactivity. PK bioequivalence between GP2015 and the originator was established in nonclinical and human studies. The study in patients with psoriasis confirmed similar efficacy and safety and comparable immunogenicity in a highly-sensitive indication. In all studies, no clinically meaningful differences between GP2015 and the originator were observed. Conclusions: Analytical, functional, nonclinical and clinical data provide a comprehensive understanding of both GP2015 and the originator and demonstrate a high level of similarity between the two products in accordance with regulatory requirements. The totality-of-the-evidence is therefore believed to justify the use of the biosimilar in the same indications as the originator. Disclosure of Interest: M. McCamish Employee of: Hexal AG, A. DaSilva Employee of: Hexal AG, R. Ernst Mayer Employee of: Sandoz Biopharmaceuticals, C. Fritsch Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG, M. Schiestl Employee of: Sandoz Biopharmaceuticals